Impact Of Social Media, Dipayal Silgadhi Municipality, Doti, Nepal - Khadka, Bharat Bahadur (DMC Research Journal, 2023)
Research paper is entitled "Impact of Social Media on the Society, Dipayal Silgadhi Municipality, Doti Nepal. It aims to analyze positive and negative impacts of social media on society. it focuses on the ways of modernization and westernization impacts, positively or negatively in the Socio-Economic, and cultural aspects imposed by Social Media. It motivated them to do something good in their careers as software developers, learn pop culture and preserve their identity. Besides, most of the youth were killing their time by surfing the internet. They were busy on the wrong sites- pornography, rape, dacoit, kidnapping and on the other hand, some people misuse social media which has negative impact on society. For Instance; cybercrime, hacking personal information and security, stretch destroy reputation, sexual harassment /rape case, divorce, bullying, disinformation, misinformation and rise of fake news, imitation of foreign culture, addiction in school children and society youths local to global level; its negative impacts on society, economy, culture, religion, psychology, family life and so on. Youths from Dipayal Silgadhi Municipality Wards five and six were selected for the study with descriptive and exploratory research design. In total, 220 youths were taken as samples determined by a purposive method. The framework of the study was based on symbolic interactionism. The data collection tools included Interview Schedule, focus group discussion (FGD), key informant interview (KII), observation and case study. It was oriented to find out the impact of social media on the society such as getting knowledge and information in a cheaper, more comfortable and faster way; it helped to be polite, collaborative and cooperative, creative, to pursue a career, links connectivity worldwide, help education and building community, develop social skill, always information and updates, advertising promotion, inspiration on all sectors, to run business and transfer skills and knowledge.